SISTEM INFORMASI PENDAFTARAN SISWA BARU BERBASIS WEB PADA SMP NEGERI 2 SIMPANG EMPAT - Torong, Yepta Efraim; Hutapea, Marlyna Infryanty; Perangin-angin, Resianta (Universitas Methodist Indonesia, 2023)
SMP Negeri 2 Simpang Empat is a junior high school located in Ndokum Siroga Village, Simpang Empat District, Karo Regency, North Sumatra Province. Information Technology has developed very rapidly with a variety of software created to modern hardware. Technological developments from time to time are getting more advanced, we can see in various aspects of life, one of which is in registering for a school, it is enough to connect to the internet and enter the intended school's website page, then we can register, so that all the activities we do become easier and more efficient. This study aims to build a school website where new students can be accepted through online media and this website is developed using the PHP programming language, MySQL database. This website can make it easier for prospective students to register for school because they only need to be connected to the internet, and registration can be done anywhere and anytime. It is also easier for schools to record new student acceptance data reports because they can check applicant data directly through the website.